Evaluation of the Complete Blood Count Parameters as Prognostic Markers for Remission of Graves’ Disease with Medical Therapy in Children - Diğdem Bezen; Eren Vurgun (Çocuk Dergisi)
Objective: Graves’ Disease (GD) is an autoimmune disease that causes hyperthyroidism. This study intended to find out whether leukocyte, neutrophil, lymphocyte, platelet counts, and neutrophil-to-lymphocyte ratio (NLR) and systemic immun-inflammation index (SII) have an association with the remission of GD. Material and Methods: Thirty-seven children who have GD have been included in the study. Anthropometric measurements, physical examination and medical history of patients were recorded. Leukocyte, neutrophil, lymphocyte, platelet counts, NLR and SII at the time of diagnosis and at the end of medical therapy were compared between patients in remission (group 1) and patients not in remission (group 2). Results: The rate of patients in remission was 54%. The presence of palpitation was higher in group 2 than group 1 (p=0.026). At the time of diagnosis, the leukocyte and neutrophil counts were higher in group 1 (p=0.001 and p=0.014, respectively). While the absence of palpitation increased the rate of remission 6.0 (95% CI: 1.1-33.1) times, the rate of remission increased 2.4 (95% CI: 1.1-5.2) times as the neutrophil count increased (p=0.041 and p=0.031, respectively). In group 2, there was an increase in leukocyte and neutrophil counts, NLR and SII after medical therapy compared to the levels at the time of diagnosis (p=0.049, p=0.008, p=0.002 and p=0.001, respectively). Conclusion: Presence of palpitation and lower neutrophil count at the time of diagnosis and increase in leukocyte count, neutrophil count, NLR and SII levels after medical therapy could be prognostic markers for not achieving remission with medical therapy of GD in children.